GEN Z DAN MARRIAGE IS SCARY: TINJAUAN HUKUM ISLAM DI DESA CANGKRINGREMBANG DEMAK - Nurikan, Izzul Laili Nafi'atin; Ngazizah, Inna Fauziatal (IAIN PONOROGO, 2025)
The “Marriage is Scary” phenomenon currently emerging among Generation Z presents two major issues: fear of making the decision to marry and doubts regarding long-term commitment. The primary causes of this concern include negative personal experiences, social pressure, and uncertainty over economic conditions, which discourage young individuals from entering the stage of marriage. Additionally, low emotional intelligence exacerbates their ability to manage conflicts and stress associated with marital life. The impact of this phenomenon is reflected in the increasing delay of marriage, the weakening of family values, and the risk of psychological issues due to the inability to cope with relationship dynamics. From the perspective of Islamic law, marriage is a sacred contract that is not merely a social agreement but also an obligation that brings blessings and inner peace when carried out with full awareness and responsibility. Islam encourages young people to prepare themselves thoroughly, including enhancing their emotional intelligence, in order to build a harmonious marriage. This research employs a qualitative method, with primary data collected from 20 Generation Z informants who experienced the “marriage is scary” phenomenon and one religious figure. The findings of the study indicate that the majority of 14 informants (70%) perceive marriage as a frightening prospect, mainly due to past trauma, economic uncertainty, career prioritization, and difficulty in trusting a partner. However, a smaller group still views marriage as a long-term commitment, although it is not considered a primary life priority at the present time.